2020
DOI: 10.1002/adhm.202002080
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Adjuvanted Molecular Activator (SeaMac) Nanovaccines Promote Cancer Immunotherapy

Abstract: Neoantigen‐based immunotherapy is a promising treatment option for many types of cancer. However, its efficacy and abscopal effect are limited by impotent neoantigens, high treatment costs, and complications due to action of adjuvants. Here, the design and synthesis of nanovaccines are reported, based on self‐adjuvanted, polymer nanoparticles with in vivo neoantigen‐harvesting and molecular activating capabilities. These nanovaccines inhibit tumor growth significantly and prolong the survival of tumor‐bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Luo et al also reported a synergistic effect between the PC7A nanovaccine and radiotherapy [ 99 ]. Self-adjuvantinged molecular activator (SeaMac) nanovaccines constructed by PC7A nanoparticles significantly inhibited tumor growth in CT26 and B16-F10 tumor models [ 100 ] (Fig. 6 ).…”
Section: Mechanism Of Self-adjuvanting Nanovaccines For Cancer Therapymentioning
confidence: 99%
“…Luo et al also reported a synergistic effect between the PC7A nanovaccine and radiotherapy [ 99 ]. Self-adjuvantinged molecular activator (SeaMac) nanovaccines constructed by PC7A nanoparticles significantly inhibited tumor growth in CT26 and B16-F10 tumor models [ 100 ] (Fig. 6 ).…”
Section: Mechanism Of Self-adjuvanting Nanovaccines For Cancer Therapymentioning
confidence: 99%
“…However, these vaccines are different because self-adjuvant nanovaccines can have abscopal effects in B16-F10 and CT26 tumors and do not require adjuvant or immune checkpoint blockers. Together, these findings can help to address some challenges facing nanovaccines, including the cost and complexity of treatment protocols [ 117 ]. Another liposome-encapsulated minimalist nanovaccine (LrTL) composing recombinant protein of trichosanthin (adjuvant) legumain peptide (antigen) was designed, and this study showed that the LrTL could induce a powerful CD8 + T cell response by activating DCs that enhance the release of IFN-γ, TNF-α, and IL-12 as immunostimulatory cytokines.…”
Section: Nanovaccines In Cancer Therapymentioning
confidence: 99%
“…This is because the immunogenicity of tumors is poor and anti-tumor T cell-mediated immune responses do not possess the necessary efficiency, resulting in a low response rate for patients with cancer [ 126 , 127 ]. Among the immunotherapy-based approaches, cancer vaccines also encounter several challenges, and their therapeutic efficiency is strongly influenced by factors such as tumor heterogeneity, low immunogenicity, poor in vivo delivery, tumor immune escape, high treatment costs, complications, and low persistence in the blood circulation [ 112 , 117 ]. To address these limitations, nanovaccines were designed and demonstrated promising efficiency in treating cancer; however, the design, manufacture, and administration of these nanovaccines also have limitations [ 128 ] ( Figure 3 ).…”
Section: Challenges Of Nanovaccines For Cancer Therapymentioning
confidence: 99%
“…In certain cases, the polymeric material itself is highly immunogenic and takes on the dual role of adjuvant and delivery vehicle. Two separate studies used the concept of adjuvant NPs, made from an inulin acetate polymer [15] and a maleimide-based polymer [16] for cancer therapy. The inulin acetate polymer activates dendritic cells (DCs) and, therefore, increases uptake of the encapsulated antigen.…”
Section: Trends In Pharmacological Sciencesmentioning
confidence: 99%